Relaciones entre asertividad y estilos cognitivos - Meza, Aníbal (1990)
Two female samples from high (HS) and low (LS) social-economic level were evaluated in Assertiveness (General GA, Defensive DA and Expansive EA) and in Cognitive Styles (Field Depedence-Independence FD-FI). Both samples differed on cognitive styles, being HS more field independent; both samples did not differed cuantitatively on GA but it could be noted some difference in the kind of assertiveness items to which they responded diferently. No difference was observed on EA but significant differences were found on DA, being HS more assertive.